2010
DOI: 10.1074/jbc.m110.165761
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of ARV1 Results in Cholesterol Retention in the Endoplasmic Reticulum and Abnormal Bile Acid Metabolism*

Abstract: Endoplasmic reticulum (ER) membrane cholesterol is maintained at an optimal concentration of ϳ5 mol % by the net impact of sterol synthesis, modification, and export. Arv1p was first identified in the yeast Saccharomyces cerevisiae as a key component of this homeostasis due to its probable role in intracellular sterol transport. Mammalian ARV1, which can fully complement the yeast lesion, encodes a ubiquitously expressed, resident ER protein. Repeated dosing of specific antisense oligonucleotides to ARV1 produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 32 publications
7
28
0
Order By: Relevance
“…Moreover, arv1 cells harbor defects in sphingolipid metabolism (Swain et al 2002), glycosylphosphatidylinositol (GPI) biosynthesis (Kajiwara et al 2008), and may harbor defects in sterol trafficking (Tinkelenberg et al 2000;Fei et al 2008). It has been suggested that Arv1 plays a role in cholesterol trafficking from the ER to plasma membrane in mammalian cells (Tong et al 2010). In the present work we show that arv1 yeast cells are mating defective.…”
Section: T He Budding Yeast Saccharomyces Cerevisiae Is Viablesupporting
confidence: 48%
“…Moreover, arv1 cells harbor defects in sphingolipid metabolism (Swain et al 2002), glycosylphosphatidylinositol (GPI) biosynthesis (Kajiwara et al 2008), and may harbor defects in sterol trafficking (Tinkelenberg et al 2000;Fei et al 2008). It has been suggested that Arv1 plays a role in cholesterol trafficking from the ER to plasma membrane in mammalian cells (Tong et al 2010). In the present work we show that arv1 yeast cells are mating defective.…”
Section: T He Budding Yeast Saccharomyces Cerevisiae Is Viablesupporting
confidence: 48%
“…Our results strongly suggest that complete loss of Arv1 protects mice from acquiring MetS and NAFLD in response to a HFD challenge. While it is still up for debate as to what is the function of ARV1 (13)(14)(15)18,19,41), evidence is accumulating that suggests it's involvement in maintaining proper sterol distribution (16,20,42,43).…”
Section: Arv1mentioning
confidence: 99%
“…Knockdown of Arv1 in HepG2 cells results in the accumulation of cholesterol in the ER and a reduction in the plasma membrane, suggesting defective sterol transport in the liver (20). Mice treated with ASOs (anti-sense oligonucleotides) to Arv1 have increases in plasma and liver bile acid levels that contain hydrophilic bile acid salts (20). The same authors observed that early loss of Arv1 caused increases in plasma PL, cholesterol, and LDL-C (low density apolipoprotein-cholesterol) levels, and a decrease in HDL-C (high density apolipoprotein-cholesterol) levels (20).…”
mentioning
confidence: 99%
See 2 more Smart Citations